If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -10x = 65 + -38x Solving 13 + -10x = 65 + -38x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '38x' to each side of the equation. 13 + -10x + 38x = 65 + -38x + 38x Combine like terms: -10x + 38x = 28x 13 + 28x = 65 + -38x + 38x Combine like terms: -38x + 38x = 0 13 + 28x = 65 + 0 13 + 28x = 65 Add '-13' to each side of the equation. 13 + -13 + 28x = 65 + -13 Combine like terms: 13 + -13 = 0 0 + 28x = 65 + -13 28x = 65 + -13 Combine like terms: 65 + -13 = 52 28x = 52 Divide each side by '28'. x = 1.857142857 Simplifying x = 1.857142857
| 4+2e=12 | | 2R^2+r=6 | | 14(-9-4x)=42 | | 6x+11=35 | | 5m+7=12 | | 3w^2+11w=4 | | V=cwh | | 0.456=-0.3(7x-31.2) | | 12b^2+5b=2 | | 4t-3=13 | | 5(x+6)=8x+5-3x+25 | | 4z^2-9z+2=0 | | v^2-14v+48=0 | | 6x+5=21-7x | | =x^3-1 | | v^2+10=7v | | v^2+10=70 | | 9x^2-3xy+6x-2y= | | 5a-10=-30 | | 20(h-50)+30=375 | | 2a^2-4a+a-2= | | r^2-3r=10 | | 3m+5=-4 | | x^2+2x=23 | | b^2-2b+3b-6= | | 3.8x=2.8x+7.0 | | -48=-5x+8-x | | 1.5y+6=y | | 3.8=0.5(8x-4.6) | | 10h^3n^3-2hn^2+14hn= | | -38=-2(-43x-24) | | 2y+5=4 |